Nanoindentation measurements of anisotropic mechanical properties of single crystalline NMC cathodes for Li-ion batteries. (January 2023) - Sharma, Nikhil; Meng, Dechao; Wu, Xianyang; de Vasconcelos, Luize Scalco; Li, Linsen; Zhao, Kejie
Abstract: Nickel manganese cobalt oxides (NMC) are the state-of-the-art cathode materials for Li-ion batteries. The layered lattice structure of NMC exhibits highly anisotropic strains upon Li intercalation, leading to particle fracture and interfacial delamination of the active particles from the conductive matrix. Such mechanical degradation becomes a crucial issue in the pursuit of high Ni-content and Co-free cathodes. Notably, the experimental information regarding the anisotropic mechanical properties of NMC cathodes is missing in the literature. In this study, we measure the stiffness constants of single crystalline NMC cathodes using environmental nanoindentation. The correlative measurements of the elastic stiffness and the lattice orientations allow us to fully determine the stiffness matrix. Furthermore, we compare the effective elastic indentation modulus, hardness, and fracture toughness of different NMC compositions. The complete information on the mechanical properties of NMC cathodes will enable accurate computational modeling and assist in designing and manufacturing durable rechargeable batteries.